Peningkatan Kualitas Standar Kebersihan Dapur Di Politeknik Sahid Jakarta (Studi Kasus Politeknik Sahid Kampus Roxy) - Bagaskoro, Budi; Saptadinata, Abi; Sulistiyowati, Reni; Nindita, Shafira; Rusnadi, Muhammad Sayyidul Adha Ali (Politeknik Sahid, 2022)
The kitchen is a room used as a place for activities to produce food, from preparing ingredients to processing food into ready-to-eat food. The kitchen has a vital role in food processing. Therefore, the kitchen and the surrounding environment must always be kept clean. Kitchen users are also required to maintain the cleanliness of the kitchen, starting from the equipment used, the place to store cooking utensils, and the place used for work must always be kept clean. The focus of this research is on examining cleanliness, which is directly related to hygiene and sanitation in the kitchen of the Sahid Polytechnic, Roxy Campus. Hygiene is the study of health. Hygiene refers to individuals, food, and beverages because it is a condition for achieving health status. Sanitation is a preventive health effort that focuses on human environmental health efforts. The purpose of sanitary hygiene is to prevent disease and poisoning. Clean hygiene is not only about taking care of individual health, food ingredients storage, and so on; it should also take care of the environment around the kitchen area. This study uses a descriptive research method with a qualitative approach. Determinants of the sample or determining the source of information using snowball sampling. Data collection techniques by observation, interviews, literature study, and documentation. The results showed that the application of cleanliness related to the kitchen hygiene of the Sahid Polytechnic Roxy Campus had not been carried out adequately based on interviews that the author conducted with three workers in the kitchen of the Sahid Polytechnic Roxy Campus. Based on the results of interviews that the author worked with workers in the kitchen of the Sahid Polytechnic, Roxy Campus, they have not been able to implement a good and correct sanitation hygiene system to maintain cleanliness and health in the kitchen environment of the Sahid Polytechnic, Roxy Campus.